EXPLORING THE IMPACT CEO DUALITY, FIRM SIZE, AND BOARD SIZE ON CAPITAL STRUCTURE BASED ON THE KNOWLEDGE MANAGEMENT DURING THE COVID-19 PANDEMIC - Tariq Tawfeeq Yousif Alabdullah; Zahraa Khaled Mohamed (ZILLZELL MEDIA PRIMA, 2023)
In light of the COVID-19 epidemic, the aim of this study is to explore the influence of CEO duality, company size, and board size on capital structure with an emphasis on knowledge management. The study was done out in Bahrain over the period of a year with a cross-sectional design, concentrating on a sample of 12 companies listed in the industrial machinery industry. Data for the year 2022 was primarily derived from annual reports. The findings of the study reveal a significant and beneficial association between board size and financial leverage (LEV). It indicates that businesses with bigger boards typically display higher amounts of financial leverage. The existence of a broader board illustrates a variety of knowledge and expertise, which may enable better capital structure decision-making. The findings highlight how important it is to take board size into account while adopting a capital structure. The research also shows an effective and beneficial connection between CEO duality and financial leverage. This suggests that businesses with a CEO who doubles as the board chairman are likely to have greater amounts of financial leverage. Due to the potential concentration of decision-making power brought on by CEO duality, there may be A rise in taking chances and reliance on financing via debt. These results highlight how crucial CEO structure is in determining capital structure. The study also discovers a significant and advantageous relationship between firm size and financial leverage. Bigger businesses frequently use larger amounts of financial leverage, which may indicate that size affects capital structure decisions. The results suggest that larger companies may have more readily available financial resources, enabling them to take on greater quantities of debt to finance their activities and investments. The study's emphasis on Bahrain's industrial machinery market during the COVID-19 epidemic offers insightful information about the particular difficulties that businesses encountered in this situation. The study adds to the body of knowledge on business finance and knowledge management in times of crisis by investigating the effects of CEO duality, company size, and board size on capital structure. Overall, this study advances knowledge of the variables affecting capital structure choices in Bahrain's industrial sector. Based to these results, firm size, CEO duality, and board size have a big impact on how much capital a company can borrow. These findings underline the significance of taking these aspects into account when designing capital structure rules and the vital function that knowledge management plays in navigating complex and uncertain business contexts, like the COVID-19 pandemic. Our understanding of the interactions between corporate governance, company features, and capital structure decisions would be improved by additional study and analysis in this area.